Blow-up Sets to a Coupled Heat System (Communications in Mathematical Research, 2021)
This paper deals with a heat system coupled via local and localized sourcessubject to null Dirichlet boundary conditions. In a previous paper of the authors, acomplete result on the multiple blow-up rates was obtained. In the present paper, wecontinue to consider the blow-up sets to the system via a complete classification forthe nonlinear parameters. That is the discussion on single point versus total blow-upof the solutions. It is mentioned that due to the influence of the localized sources,there is some substantial difficulty to be overcomed there to deal with the single pointblow-up of the solutions.